2007
DOI: 10.1111/j.1600-079x.2007.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin antagonizes the intrinsic pathway of apoptosis via mitochondrial targeting of Bcl‐2

Abstract: We have recently shown that melatonin antagonizes damage-induced apoptosis by interaction with the MT-1/MT-2 plasma membrane receptors. Here, we show that melatonin interferes with the intrinsic pathway of apoptosis at the mitochondrial level. In response to an apoptogenic stimulus, melatonin allows mitochondrial translocation of the pro-apoptotic protein Bax, but it impairs its activation/dimerization The downstream apoptotic events, i.e. cytochrome c release, caspase 9 and 3 activation and nuclear vesiculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
78
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 49 publications
9
78
0
2
Order By: Relevance
“…Alternative mechanisms have been proposed; in U937 monocytes, melatonin reduces apoptosis via intracellular signal transduction stimulated by interaction with MT1/MT2 plasma membrane receptors [23]. However, the majority of reports indicate that the anti-apoptotic of melatonin occurs by acting on the abundance of the two main members of the Bcl-2 family, namely the pro-apoptotic Bax and the anti-apoptotic Bcl-2 proteins [108].…”
Section: Page 9 Of 29mentioning
confidence: 99%
See 4 more Smart Citations
“…Alternative mechanisms have been proposed; in U937 monocytes, melatonin reduces apoptosis via intracellular signal transduction stimulated by interaction with MT1/MT2 plasma membrane receptors [23]. However, the majority of reports indicate that the anti-apoptotic of melatonin occurs by acting on the abundance of the two main members of the Bcl-2 family, namely the pro-apoptotic Bax and the anti-apoptotic Bcl-2 proteins [108].…”
Section: Page 9 Of 29mentioning
confidence: 99%
“…Melatonin is able to shift the balance towards a cell-protective state [108]. Indeed, many studies have demonstrated that its anti-apoptotic effect involves the down-regulation of Bax [110][111][112][113] and /or the up-regulation of Bcl-2 [110,114,115] that occurs via activation of NF-B [115].…”
Section: Page 9 Of 29mentioning
confidence: 99%
See 3 more Smart Citations